PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI SATUAN DEBIT MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE PROBLEM SOLVING - Widad Widad (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
It is common knowledge that students experience difficulties in learning mathematics, especially the discharge unit material for class VI.A SD Negeri 28 Palembang. In mathematics, students in class VI.A averaged a score of 59.60. To be considered successful, a minimum of 70 students must complete the assignment. This research was conducted at SD Negeri 28 Palembang. The research was conducted from August to October 2019. Class VI.A students at SD Negeri 28 Palembang a total of 25 students were the subjects of this study. Nevertheless, class teachers and other colleagues participated in this study. The Problem Solving learning model has the potential to improve student learning outcomes, as evidenced by an increase in student learning completeness in each cycle and pre-cycle (30 percent), cycle I (63.33 percent), and cycle II (86.67 percent) based on the results of research that has exposed for two cycles. actively, solve real-world problems, identify and conduct investigations, interpret and evaluate observational findings, and stimulate students' thinking development as they progress toward problem solving.